Void spot assay visualization optimization for use of Void Whizzard in rats (Rattus norvegicus) - Hannah Ruetten; Jadyn Bothe; Shannon Lankford; Gopal Badlani; James Koudy Williams (Physiological Reports)
Abstract Void spot assay (VSA) noninvasively evaluates urination. This study optimizes VSA by comparing post‐assay paper visualization techniques: bright field light (BF), ultraviolet light (UV), and ninhydrin spray (N). Male rats were placed in filter paper lined cages for 4 h. After the assay, all papers were dried. BF images were photographed (digital camera). UV images were captured using a Darkroom ultraviolet imaging cabinet. Papers were sprayed with ninhydrin and photographed (digital camera). All images were converted to binary for analysis with Void Whizzard. UV versus BF significantly differed in area. All three groups significantly differed in overall spot count and spots 0–0.1 cm2. UV versus N and UV versus BF significantly differed in 0.1–0.25 cm2 spots, UV versus N in 0.25–0.5 cm2, and N versus BF in spots 0.5–1 cm2. Overall BF visualization proved difficult. N provided an ideal way to highlight urine and image with a digital camera. Human fingerprints from pre‐assay handling of paper interfered with the analysis of the smallest sized spots; however, there were no differences in the detection of larger spots, spot distribution, or overall spot area. This study contributes to the development of a standardized VSA protocol for assessing bladder function in rodent models.